1991
DOI: 10.1128/aem.57.10.2975-2980.1991
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic relationships among strains of the anaerobic bacterium Bacteroides ruminicola determined by DNA and extracellular polysaccharide analysis

Abstract: DNA and extracellular polysaccharide (EPS) analyses were performed on 14 strains of Bacteroides ruminicola. The guanine-plus-cytosine (G+C) base contents, determined from the buoyant densities of chromosomal DNAs, showed a broad range of values, from 37.6 to 50.9 mol%. DNA hybridization showed generally low DNA relatedness among the strains. Seven strains formed two groups of closely related bacteria consisting of five (group 1) and two (group 2) strains, and another strain, E42g, showed moderate relatedness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…P. ruminicola 20-78, 20-63, 23, and 118B produced less than onethird the CMCase activity of B 1 4, and Western blots indicated that the other strains that produced CMCases did not react with B 1 4 CMCase antiserum. These results support the idea that P. ruminicola is a highly divergent species that needs further reclassification (2,11). Strains B 1 4, TC1-1, TF1-3, and TS1-5 could be a separate species.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…P. ruminicola 20-78, 20-63, 23, and 118B produced less than onethird the CMCase activity of B 1 4, and Western blots indicated that the other strains that produced CMCases did not react with B 1 4 CMCase antiserum. These results support the idea that P. ruminicola is a highly divergent species that needs further reclassification (2,11). Strains B 1 4, TC1-1, TF1-3, and TS1-5 could be a separate species.…”
Section: Discussionsupporting
confidence: 83%
“…P. ruminicola strains have as little as 20% DNA homology, and the B 1 4 strain is the most genetically distinct strain (11). The B 1 4 strain produces 88-and 82-kDa CMCases (13), while most other P. ruminicola strains produce smaller CMCases (1,16).…”
mentioning
confidence: 99%
“…A similarly high proportion of cultured isolates from the rumen have been reported to be Prevotella strains in some studies [14–16]. The genotypic and phenotypic variability within cultured strains of rumen Prevotella has been demonstrated [17,18] and recently the redefinition of the species P. ruminicola and the elevation of three different groups of strains to the species level was proposed [19]. Several major branches of the phylogenetic trees constructed from randomly cloned Prevotella/Bacteroides sequences lack any sequences derived from cultured strains [7,8].…”
Section: Introductionmentioning
confidence: 97%
“…bovis population, then it needs to be determined whether the populations that are likely to be encountered in the field are genetically homogenous and whether it is possible that a small number of phages can be found that will infect across the range likely to be encountered. Other common rumen bacteria, such as Prevotella ruminicola (Hudman and Gregg 1989;Mannarelli et al 1991) and Butyrivibrio fibrisolvens (Mannarelli 1988;Hudman and Gregg 1989;Forster et al 1996) have been found to be genetically heterogenous, comprising a variety of genetically distinct species and even genera. Streptococcus bovis strains appear much more closely related to each other, with ruminal strains likely to be representing at most two species (Nelms et al 1995).…”
Section: Introductionmentioning
confidence: 99%